Development of a Collaborative Leadership Model in Conflict Management in Secondary Schools: A Systematic Literature Review and Its Implications for Vocational and Senior High Schools in West Sumatra - Sunarti Al Mondar; Azizah Dwi Sa’diyah; Nurizrah Gistituati; Rusdinal; Nellitawati; Anisah; Merika Setiawan; Irsyad (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Conflicts in senior high schools (SMA) and vocational high schools (SMK) in West Sumatra often arise from differences in academic policies and organizational pressures, but the lack of a specific collaborative leadership model is a major research gap. This study aims to develop a conceptual model of collaborative leadership in conflict management. Using a systematic literature review (SLR) with the PRISMA protocol, the population included publications from 2015–2025 in Scopus, Google Scholar, and national journals; the sample was purposively selected based on relevance to Indonesian secondary schools. The search protocol, using keywords such as